Impact Property of Low-Activation Vanadium Alloy NIFS-HEAT-2 After Electron Beam Welding and Neutron Irradiation. (17th November 2017) - Nagasaka, Takuya; Fu, Haiying; Kometani, Nobuyuki; Miyazawa, Takeshi; Muroga, Takeo; Watanabe, Hideo; Yamazaki, Masanori; Toyama, Takeshi
Abstract: In order to investigate the effect of post-weld heat treatment (PWHT) and post-irradiation annealing (PIA), electron-beam-weld specimens of the reference low activation vanadium alloy, NIFS-HEAT-2, were neutron-irradiated to a fluence of 7.62 × 10 23  neutron m −2 (E > 1 MeV) at 563 K in Belgian Reactor-2. In the present experiments, unexpected oxidation of the surface of the samples occurred during the neutron irradiation, and significantly degraded impact properties of the weld metal, while the degradation was not significant for the base metal. The removal of the oxidized layer by electro-polishing improved the impact properties of the weld metal. Although complete removal of the oxidized layer could not be confirmed, it is revealed that impact absorbed energy of the weld metal with post-weld heat treatment at 1073 K was comparable to that of the base metal after the post-irradiation polishing. In other words, irradiation embrittlement of the weld metal was successfully suppressed by the PWHT. PIA at 773 K and above was effective to recover the irradiation hardening and irradiation embrittlement. Mechanisms of the irradiation hardening, irradiation embrittlement and its recovery were discussed.